Extending Pension Coverage to the Informal Sector in Africa - Guven, Melis (World Bank, Washington, DC, 2019)
The coverage of pension systems in the Africa region is limited to the small segment of the population in the formal sector. Coverage is thin partly because traditional contributory pension schemes are not responding to the needs of the informal sector. As a result, a large share of the region’s adult population has no access to contributory pension schemes during their working lives. This means they will not be eligible for a pension. It also means the elderly coverage gap will persist in most countries. Expanding coverage to a larger group of workers is especially important because the elderly is now often cared for by their children. As the children move to cities, their ties to the elderly and home villages weaken. As a result, the elderly may be left behind with fewer resources.